Pelatihan Penggunaan Platform Digital sebagai Media Pembelajaran Daring di Masa Pandemi Covid19 untuk Sekolah Dasar - Rini Indrayani (Muria Jurnal Layanan Masyarakat, 2021)
Early in 2020, the world was shocked by a new type of influenza virus that was first identified in the city of Wuhan, Hubei province, China at the end of 2019. The international health organization, the World Health Organization (WHO), declared the urgency of health problems related to the SARS-Cov virus. 2 which later became known as COVID-19. Efforts to suppress the number of cases spread have been carried out in various ways, one of the efforts made by learning at all levels of schools to be transferred to the digital realm or known as online learning. Due to the lack of time allotted for preparation, a number of educators and students are deemed not ready to implement online type learning. . Therefore, various efforts are needed to help broaden the insight of educators and students for the smoothness of the online learning process such as training on the use of online learning digital platforms. The output of training in using this digital platform can be in the form of additional insights and experiences for training participants. Various types of platforms are introduced to teachers as trainees. However, from the survey results, the platform in the form of video conferencing was most in-demand with an interest percentage of 89.47%.